Implikasi Pendidikan dari QS. Az-Zumar ayat 9-10 tentang Taat dan Bertakwa Kepada Allah terhadap Upaya Pembinaan Akidah dan Akhlak - Hadist Dwi Fajri Muhammad Darmawan; Eko Subiantoro; Helmi Aziz (Bandung Conference Series: Islamic Education, 2023)
Abstract. The role of faith and morals has a very important position in making us as educators able to teach and provide a good understanding to a child. The reason for this research was raised because it was motivated by several phenomena that occurred in modern times, namely cases of deviations in faith and morals that occurred. Through this, it is necessary to develop aqeedah and develop akhlak. This study aims to find out the opinion of the mufassir, the essence of the verses in QS. Az-Zumar verses 9-10, the opinion of experts regarding the development of aqeedah and morality, to find out the implications of qs az-zumar verses 9-10 about obeying and fearing Allah SWT for the development of akidah and morality. This research uses a qualitative approach and a descriptive-analytic method with a literature study. The content of this verse is that these believers obey Allah, they carry out the night prayer while he is afraid and hopes, they are people who think about the verses of Kauniyah, maintain a relationship with Allah, and the command to emigrate to develop goodness and be patient in facing it. According to coaching experts, what can be done is to direct feelings, train thoughts, teach the concept of the pillars of Islam, study commendable behavior and educate firmness in faith and be ready to sacrifice for it. The implications of QS. Az-Zumar verses 9-10 this is that a Muslim must seek guidance on feelings and become a thinking person so that he does not experience deviations, educators, namely parents and teachers can learn an understanding of carrying out true faith so that they can prohibit children regarding matters of faith, giving understanding of spiritual intelligence, giving advice to children regarding true faith and noble morals. Abstrak. Peran akidah dan akhlak memiliki kedudukan yang sangat penting menjadikan kita sebagai pendidik untuk bisa mengajar dan memberikan pemahaman yang baik kepada seorang anak Alasan penelitian ini diangkat karena dilatarbelakangi oleh beberapa fenomena yang terjadi di zaman modern yaitu maraknya kasus penyimpangan akidah dan akhlak yang terjadi. Melalui hal tersebut maka dibutuhkan pembinaan akidah dan pembinaan akhlak. Penelitian ini bertujuan untuk mengetahui pendapat para mufassir, esensi ayat yang ada pada QS. Az-Zumar ayat 9-10, pendapat para ahli mengenai pembinaan akidah dan akhlak, serta mengetahui implikasi pendidikan dari QS. Az-Zumar ayat 9-10 tentang taat dan bertakwa kepada Allah terhadap upaya pembinaan akidah dan akhlak. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif-analitik dengan studi literatur. Hasil penelitian dari ayat ini ialah orang mukmin tersebut taat kepada Allah mereka melaksanakan sholat malam, mereka ialah orang yang berfikir merenungi ayat-ayat kauniyah, bertakwa kepada Allah, dan perintah untuk berhijrah mengembangkan kebajikan serta bersabar menghadapinya. Menurut para ahli pembinaan yang dapat dilakukan yaitu melakukan pengarahan terhadap perasaan, melakukan pembinaan pemikiran, mengajari konsep rukun islam membiasakan perilaku terpuji dan mendidik keteguhan dalam akidah. Implikasi dari QS. Az-Zumar ayat 9-10 ini ialah seorang muslim harus berupaya melakukan pengarahan terhadap perasaan serta menjadi orang yang berfikir agar tidak mengalami penyimpang, pendidik yaitu orang tua dan guru dapat mempelajari pemahaman mengenai akidah yang benar agar dapat mengajarkan kepada anak mengenai persoalan akidah, memberikan pemahaman berkaitan kecerdasan spiritual, memberikan nasehat berkenaan akidah dan akhlak yang mulia.